2013
DOI: 10.1016/j.bar.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Value creation and business models: Refocusing the intellectual capital debate

Abstract: There is currently significant debate worldwide regarding business reporting. The concept of the 'business model' has entered into the discourse, as has the concept of 'integrated reporting', adding to the established debate regarding accounting for intangible assets and, more generally, intellectual capital (IC). Despite the tradition of extensive interdisciplinary borrowing in accounting, relevant literatures on business models and on modern managerial perspectives on competitive advantage have, to date, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(231 citation statements)
references
References 43 publications
6
211
0
14
Order By: Relevance
“… Collaboration between firms and other stakeholders: Collaboration between firms and other key stakeholders is becoming more important (Lowitt [45]). Value is no longer created by firms acting alone; instead firms are acting together with external parties through informal arrangements or formal alliances (Beattie and Smith [31], Bocken, et al [46]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Collaboration between firms and other stakeholders: Collaboration between firms and other key stakeholders is becoming more important (Lowitt [45]). Value is no longer created by firms acting alone; instead firms are acting together with external parties through informal arrangements or formal alliances (Beattie and Smith [31], Bocken, et al [46]). …”
Section: Discussionmentioning
confidence: 99%
“…Business models have received important attention in literature and business and it is increasingly suggested that business model innovation increases business performance (Chesbrough [27], Zott et al [28]). The literature offers different views on the business model: Margretta's [29], Zott and Amit [30] and Beattie and Smith [31] describe business models as a holistic description on 'how a firm does business'. Teece [32] proposed that a business model articulates how the company will convert resources and capabilities into economic value.…”
Section: The Business Model and Value Proposition Of Each Type Of Sermentioning
confidence: 99%
“…Business model innovation is defined as a discipline supporting the change of value proposition to customers (Bocken et al, 2014), involving the change of the way a business is run (Zott and Amit, 2013), and considering a large number of stakeholders and a broad value-network going well beyond the existing firm perspective (Beattie and Smith, 2013;Zott and Amit, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that while the opening sentence of Beattie and Smith (2013) The practice statement is not an IFRS. Consequently, entities are not required to comply with the practice statement, unless specifically required by their jurisdiction.…”
Section: The Continuing Case For Narrative Reportingmentioning
confidence: 99%
“…Its re-emergence is closely related to the growing interest in integrated reporting (IR) (BIS, 2010;IIRC, 2011IIRC, , 2012IIRC, , 2013, within which narrative reporting has a major role to play, including in connection with the business model that is identified as being central to this approach to business reporting (EFRAG, 2010;ICAEW, 2010;Haslam et al, 2012;Leisenring et al, 2012;Beattie and Smith, 2013). Narrative reporting also played a significant role within the intellectual capital statement (ICS) reporting framework that emerged from the Danish Guideline Project (DGP) (1997)(1998)(1999)(2000)(2001)(2002) (DATI, 2000;Mouritsen et al, 2001Mouritsen et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%